La « grève » féminine du sexe dans la France du XVe siècle, un exemple de révolte impossible contre la domination masculine ? - Adrien Dubois (Genre, Sexualité et Société)
Feminine consent to sexual intercourse is a genuine historiographical problem. According to judicial sources from the end of the Middle Ages, rapists put to trial would blame their victims’ lewdness, thus implying their consent. At the same time, consensualism, an indispensable condition to Christian marriage based on the obligation of a conjugal duty, did not leave much space for the notion of consent. The remission letters that are presented in this article nevertheless expose cases in which women remain adamant in their refusal, and their punishments. This raises the wider question of the options left to those women to defend themselves, and leads us to wonder whether they truly may comport themselves as subjects entitled to say no.